2021
DOI: 10.1126/sciadv.abe0465
|View full text |Cite
|
Sign up to set email alerts
|

Moonstruck sleep: Synchronization of human sleep with the moon cycle under field conditions

Abstract: Before the availability of artificial light, moonlight was the only source of light sufficient to stimulate nighttime activity; still, evidence for the modulation of sleep timing by lunar phases is controversial. Here, we use wrist actimetry to show a clear synchronization of nocturnal sleep timing with the lunar cycle in participants living in environments that range from a rural setting with and without access to electricity in indigenous Toba/Qom communities in Argentina to a highly urbanized postindustrial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Starting with the early 20th century, numerous scientific studies have shown that the reproductive behavior and sexual maturation of animals as diverse as corals, polychaetes, echinoderms, fishes or turtles are synchronized by the lunar cycle 1, [3][4][5][6][7] . In addition, lunar timing effects have also been documented outside the marine environment 8,9 , and recently uncovered correlations of human sleep and menstrual cycle properties with moon phases have re-initiated the discussion of an impact of the moon even on human biology 10,11 . As recently documented for corals, desynchronization of these reproductively critical rhythms by anthropogenic impacts poses a threat to species survival 12 .…”
Section: Main Textmentioning
confidence: 99%
“…Starting with the early 20th century, numerous scientific studies have shown that the reproductive behavior and sexual maturation of animals as diverse as corals, polychaetes, echinoderms, fishes or turtles are synchronized by the lunar cycle 1, [3][4][5][6][7] . In addition, lunar timing effects have also been documented outside the marine environment 8,9 , and recently uncovered correlations of human sleep and menstrual cycle properties with moon phases have re-initiated the discussion of an impact of the moon even on human biology 10,11 . As recently documented for corals, desynchronization of these reproductively critical rhythms by anthropogenic impacts poses a threat to species survival 12 .…”
Section: Main Textmentioning
confidence: 99%
“…Reasons for this intra-individual variability should be investigated. Longer-term intra- and inter-individual variability is affected by photoperiod in humans and other animals, with longer sleep episodes across the month (with nighttime light from the moon) ( Casiraghi et al, 2021 ) and during seasons with longer durations of darkness [e.g., ( Wehr, 1991 ; van Hasselt et al, 2020 )].…”
Section: Discussionmentioning
confidence: 99%
“…Infradian metaplasticity is a form of iterative metaplasticity repeating on a longer-than-daily timescale (Figure 1, lower panel). Circalunar (approximately one lunar cycle) rhythms, including moon-phase-dependent fluctuations in sleep quality (Casiraghi et al, 2021) and the human ovulatory cycle (Helfrich-Förster et al, 2021), may contribute to infradian metaplasticity. We have already discussed an example of how sleep may directly influence neuroplastic capacity (Noya et al, 2019).…”
Section: Iterative Metaplasticity On a Longer-than-daily Timescale: I...mentioning
confidence: 99%